The Correspondence of Charles Darwin - Darwin, Charles 1809-1882 (Cambridge University Press, 2016)
This volume is part of the definitive edition of letters written by and to Charles Darwin, the most celebrated naturalist of the nineteenth century. Notes and appendixes put these fascinating and wide-ranging letters in context, making the letters accessible to both scholars and general readers. Darwin depended on correspondence to collect data from all over the world, and to discuss his emerging ideas with scientific colleagues, many of whom he never met in person. The letters are published chronologically: volume 24 includes letters from 1876, the year in which Darwin published Cross and Self Fertilisation in the Vegetable Kingdom, and started writing Forms of Flowers. In 1876, Darwin's daughter-in-law, Amy, died shortly after giving birth to a son, Bernard Darwin, an event that devastated the family. The volume includes a supplement of 182 letters from earlier years, including a newly discovered collection of letters from William Darwin, Darwin's eldest son.
Keywords: Darwin, Charles, -- 1809-1882 -- Correspondence.